Analisis Penggunaan Bahasa Baku pada Siswa Kelas IV SD Melalui Keterampilan Menulis Karangan Narasi - Dian Ratna Suryandari; Haryadi Haryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the use of standard language in fourth grade students of SD Negeri Giling 03 Pati through narrative essays. This research is a qualitative research by applying descriptive method in the process. Based on the research, it was found that 1) The writing results of fourth grade students at SD Negeri 03 Giling Pati are more than 50% of the number of students who are less in using standard language, 2) Students in using standard words at school, at home, and in everyday life rarely done so that students are not accustomed to writing using the correct standard words according to the rules, 3) When writing students do not use standard words influenced by external and internal factors. Conclutions, external factors that influence students in writing not using standard words consist of: (a) Teacher's mastery of the standard word is lacking, (b) Development of information and communication technology, and (c) Student association and living environment. Internal factors consist of: (a) writing practice using standard words that are still lacking, (b) students' knowledge and understanding of standard words are still lacking, (c) students' interest in writing is low, and (d) students are not careful. Keywords: Standard Language, Writing Skills, Narrative Writing